2023
DOI: 10.1111/tgis.13101
|View full text |Cite
|
Sign up to set email alerts
|

Towards a spatio‐temporal multicriteria evaluation method: A suitability analysis of residential units in a 3D urban environment

Kendra Munn,
Suzana Dragićević

Abstract: Spatial multi‐criteria evaluation (MCE) techniques aid urban planning management by analyzing decision problem alternatives for solutions to help inform decision‐making. However, there is a lack of such methods that incorporate the temporal dimension, an important factor when analyzing the dynamic urban landscape and decisions surrounding its changes. A novel spatio‐temporal MCE approach is proposed that operates in three‐dimensional (3D) space and time to identify changing suitability values of decision alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Therefore, it is necessary to compare the ecosystem components crossing comparable structure levels quantitatively (Fábregas-Tejeda and Vergara-Silva 2018; Jafary et al 2018). Using multicriteria evaluation, Gunaydin et al (2022) and Munn and Dragićević (2023) demonstrated the quality of the analysis when they compared different environmental systems at various scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to compare the ecosystem components crossing comparable structure levels quantitatively (Fábregas-Tejeda and Vergara-Silva 2018; Jafary et al 2018). Using multicriteria evaluation, Gunaydin et al (2022) and Munn and Dragićević (2023) demonstrated the quality of the analysis when they compared different environmental systems at various scales.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, we aimed to identify multiple components of abiotic and biotic factors at various levels and to create the top, focal, and lower-level ecosystem classifications for a territory ecoregion. Furthermore, we evaluated some hierarchical ecosystem theories (Kolasa and Pickett 1989;Wu and David 2002;Wu 2013;Valérie 2017) and accessed the LECs using classic ecosystem components and multicriteria evaluation (Anderson and Dragićević 2020;Yuan et al 2022;Munn and Dragićević 2023) at the global continental scale.…”
Section: Introductionmentioning
confidence: 99%